2020
DOI: 10.1186/s12967-020-02310-2
|View full text |Cite
|
Sign up to set email alerts
|

LTBP1 promotes esophageal squamous cell carcinoma progression through epithelial-mesenchymal transition and cancer-associated fibroblasts transformation

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is one of the most prevalent cancers worldwide. Due to its high morbidity and mortality rates, it is urgent to find a molecular target that contributes to esophageal carcinogenesis and progression. In this research, we aimed to investigate the functions of Latent transforming growth factor β binding protein 1(LTBP1) in ESCC progression and elucidate the underlying mechanisms. Methods: The tandem mass tag-based quantitative proteomic approach was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…There are two most common histological subtypes: Squamous cell carcinoma and adenocarcinoma. Despite marked improvements of therapies, the overall survival rate of patients with esophageal cancer remains unsatisfactory ( 2 ). The poor prognosis of esophageal cancer is attributed to early metastasis ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are two most common histological subtypes: Squamous cell carcinoma and adenocarcinoma. Despite marked improvements of therapies, the overall survival rate of patients with esophageal cancer remains unsatisfactory ( 2 ). The poor prognosis of esophageal cancer is attributed to early metastasis ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In EC, the upregulation of FN1 expression is regulated by STAB1 (Song et al, 2017 ). A study also reported that the suppression of LTBP1 can attenuate cancer-associated fibroblast (CAF) transformation and inhibit FN1 in ESCC (Cai et al, 2020 ). The elevated FN1 expression may also promote the occurrence of cancer, including breast cancer (Dorman et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of CAFs in ESCC patients is associated with increased micro-vessel density, TAMs, and EMT, which are critical for ESCC invasion and metastasis ( 83 , 84 ). A number of genes have been shown to promote ESCC invasion and metastasis via the CAF transformation and EMT process ( 85 , 86 ). Also, it has been demonstrated that CAFs promote ESCC invasion by secreting hepatocyte growth factor (HGF) and infiltrating MDSCs ( 87 , 88 ).…”
Section: The Role Of Tumor Microenvironment In Esophageal Squamous Ce...mentioning
confidence: 99%